Quantification of key factors and hazard classification of “coal wall” stability under high-intensity mining - Shaohong YAN; Bo XUE (Meitan xuebao)
Aiming at the engineering problem of coal wall rib spalling under high-intensity mining that restricts normal mining and intelligent prediction and control, based on the proposed “combined short cantilever beam-articulated rock beam structure”, the geological mining factors and four mining technical factors that affect the stability of the coal wall were put forward. Using a method that combines theoretical analysis, numerical simulation, and physical similarity tests, the influence of key factors on the stability of coal wall in high-intensity mining was analyzed. A short beam model of the plastic yield zone of the coal wall was constructed, and a Chebyshev polynomial was constructed to solve the model and obtain the expression of the deflection curve under complex loads. The expression analysis shows that the coal wall rib spalling is greatly affected by geological mining factors and mining technology factors. Taking the Caojiatan large mining height working face as the engineering background, an orthogonal test of mining technical factors was constructed. Numerical simulation and physical similarity experiments were used to study the sensitivity of various mining technology factors to the stability of the coal wall. An index was proposed to measure the degree of stability based on the plastic zone ratio η between the area of the plastic zone in the coal wall and the area under investigation, and the regression equation between various factors and the plastic zone ratio coefficient η of the coal wall was derived. Based on this, the relationship between the coal wall stability and technical factors of the large mining height fully mechanized caving working face in the Caojiatan Coal Mine was quantitatively obtained, and the risk classification of the coal wall rib spalling was given. Combined with physical similarity experiments, it was verified that adjusting mining technical factors can control the range and depth of coal wall rib spalling to a certain extent, which provides a theoretical basis for the intelligent decision-making on coal wall stability in the fully mechanized caving working face with large mining height. This research method can also be used in other working faces.